The Influence of Digital Leadership Style and Employee Engagement on Employee Performance at Bank BJB - Muhammad Fikri Fauzi; Leni Rohida (Jurnal Polisci, 2026)
Background. The banking sector must prioritize digital transformation as a strategic necessity. The success of digital transformation is contingent not only upon the preparedness of the technological infrastructure but also on the caliber of leadership and employee engagement. Aims. This study aims to assess the influence of digital leadership and employee engagement on employee performance at Bank BJB, and to examine the mediating role of employee engagement in these relationships. Methods. Data analysis encompasses validity and reliability assessments, descriptive statistics, Pearson correlation, multiple linear regression analysis, and path mediation analysis.Outcome. The study's findings demonstrate that digital leadership has a substantial and affirmative effect on employee performance, that digital leadership greatly enhances employee engagement, and that employee involvement markedly improves employee performance. Conclusion. Employee engagement partially mediated the effect of digital leadership on employee performance, with an indirect effect (0.756) that exceeded the direct effect (0.285), resulting in the comprehensive model accounting for 64.1% of the variance in employee performance.β = 0.668, p < 0.001, R² = 0.550; β = 0.598, p < 0.001, R² = 0.472; β = 1.264, p < 0.001, R² = 0.575